Cryptotanshinone enhances neurite outgrowth and memory via extracellular signal-regulated kinase 1/2 signaling. (February 2020) - Kwon, Huiyoung; Cho, Eunbi; Jeon, Jieun; Kim, Kyung Sook; Jin, Ye Lim; Lee, Young Choon; Yun, Jeanho; Park, Se Jin; Yi, Jee Hyun; Kim, Dong Hyun
Abstract: Neurite outgrowth is important process in synaptic formation and neuronal development. Many previous studies reported that natural compounds as well as neurotrophins induce neurite outgrowth through various signaling pathways. In this study, we tested the effect of cryptotanshinone (CPT), a constituent of Salvia miltiorrhiza Bunge, on neurite outgrowth using neuro2a cell line, a mouse neuroblastoma cell line. And then, we examined the effect of CPT on learning and memory. We first found that CPT facilitated neurite outgrowth in a concentration-dependent manner. Although CPT induced MTT reduction, CPT did not induce LDH release. Moreover, CPT suppressed cell proliferation. CPT increased ERK1/2 phosphorylation and ERK1/2 inhibitor blocked CPT-facilitated neurite outgrowth. CPT also enhanced learning and memory without affecting basal sensory conditions and increased ERK1/2 phosphorylation in the hippocampus in a dose-dependent manner. These results demonstrate that CPT facilitates neurite outgrowth and enhances learning and memory, which may be mediated by facilitating ERK1/2 signal. Highlights: CPT facilitated neurite outgrowth in a concentration-dependent manner. CPT increased ERK1/2 phosphorylation. ERK1/2 inhibitor blocked CPT-facilitated neurite outgrowth. CPT enhanced learning and memory without affecting basal sensory conditions. CPT increased ERK1/2 phosphorylation in the hippocampus in a dose-dependent manner.